Democracy and education - Dewey, John, 1859-1952 (2024)
"Democracy and Education is philosopher John Dewey's argument for the centrality of learning and education in human life. For over a century, people around the world have been reading Democracy and Education; Dewey remains central to global thinking about the philosophy of education, democratic political theory, pedagogy, sociology, and education public policy. That said, there is a demand for a new edition of Democracy and Education, particularly one targeted at undergraduates in social science. The current editions on the market are a 1980 university press edition with an outdated introduction and inexpensive, poor quality paperback reproductions without an editorial apparatus and issues with legibility. Dewey's ideas are intuitive and are increasingly influential in sociology, which in some circles has taken an explicitly pragmatist turn, but he is a difficult writer to read without expert guidance. He draws on influences that may not be readily known to contemporary readers and uses words that have come to mean other things. In this new edition, Nicholas Tampio will contain a substantial introduction to the book, framing introductions to each chapter, and a set of discussion questions and a bibliography following each chapter, designed to make Democracy and Education substantially easier for students to read and comprehend"--
Keywords: Education -- Philosophy; Education -- Social aspects; Democracy and education